2013
DOI: 10.3389/fncel.2013.00072
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and pharmacological manipulations of the serotonergic system in early life: neurodevelopmental underpinnings of autism-related behavior

Abstract: Serotonin, in its function as neurotransmitter, is well-known for its role in depression, autism and other neuropsychiatric disorders, however, less known as a neurodevelopmental factor. The serotonergic system is one of the earliest to develop during embryogenesis and early changes in serotonin levels can have large consequences for the correct development of specific brain areas. The regulation and functioning of serotonin is influenced by genetic risk factors, such as the serotonin transporter polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 177 publications
(199 reference statements)
1
34
0
Order By: Relevance
“…Later, it was shown that genetic SERT deficiency affected S1 organization similarly in rodent. These alterations are not only structural but also impair whisker-mediated perception [10]. Hyper-activation of the 5-HT 1B receptor, transiently expressed on TCAs during development, plays a key role in this process.…”
Section: Serotonin and Axonal Development Within The Cerebral Cortexmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, it was shown that genetic SERT deficiency affected S1 organization similarly in rodent. These alterations are not only structural but also impair whisker-mediated perception [10]. Hyper-activation of the 5-HT 1B receptor, transiently expressed on TCAs during development, plays a key role in this process.…”
Section: Serotonin and Axonal Development Within The Cerebral Cortexmentioning
confidence: 99%
“…Developmental perturbations impacting the maturation of cortical circuits can trigger neuropsychiatric disorders [8][9][10]. Sensitive periods or windows of vulnerability have been demonstrated in various processes in particular for the rodent sensory systems as well as in the modulation of complex behaviours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These drugs are able to modulate the expression of many genes involved in processes such as proliferation, apoptosis, neuronal differentiation and migration, synaptogenesis, and synaptic activity [229]. Exposure to selective serotonin reuptake inhibitors (SSRI) in depressed pregnant women might be involved in the etiology of autism, as well as the prenatal valproic acid (VPA) exposure, which is also thought to interfere with serotonin levels [230], by disruption of early serotonergic neuronal development [231] or via the reduction of PTEN level [232].…”
Section: Toxic Exposures Teratogens and Medicationsmentioning
confidence: 99%
“…Finally published animal studies consistently show that pups born to animals administered antidepressants during pregnancy show a range of behavioral changes indicative of reduced social confidence and communication deficits consistent with a diagnosis of neurodevelopmental spectrum disorders in humans [54][55][56][57][58][59][60][61].…”
Section: Healy Et Al / Link Between Ssris In Pregnancy and Autistmentioning
confidence: 99%